Nano-drug hydrogel composite system capable of being perfused by bladder and application of nano-drug hydrogel composite system

Through the use of hydrogel and urease-modified nanoparticle complex, the problems of short drug residence time and poor penetration of urinary barriers in bladder perfusion treatment are solved, efficient directed drug movement and deep penetration are achieved, and the preparation process is simplified , improves the therapeutic effect.

CN119112761APending Publication Date: 2024-12-13杭州祥实生物科技有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310841832.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In bladder perfusion treatment, the drug resides in the bladder for a short time and is difficult to penetrate the urothelial barrier, resulting in limited efficacy. The preparation of existing Janus micro-nanomotors is complex and the movement is uncontrollable, making it difficult to achieve efficient directional movement.

Method used

Using a nanoparticle complex modified by hydrogel and urease, the sol-gel state transition is achieved through temperature changes. Combined with symmetric modification technology, the nanoparticles achieve orderly and directional movement under the urea concentration gradient to improve the mucus adhesion of drugs and Permeability.

Benefits of technology

It improves the accumulation and absorption of drugs at the bladder lesions, enhances the permeability of bladder tissue, simplifies the preparation process, improves the yield and exercise controllability, and provides the possibility of clinical transformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119112761A_ABST
    Figure CN119112761A_ABST
Patent Text Reader

Abstract

The invention provides a nano-drug hydrogel composite system for bladder perfusion and application thereof, and provides a new concept for bladder perfusion drugs, i.e., hydrogel is used as a drug loading platform, and a concentration gradient is formed through permeation of urea; therefore, the nano-particles modified with the'motor 'in the hydrogel generate directional movement due to different pushing forces on the two sides. And the disorderly moving nano-particles are limited by external conditions, so that the aim of orderly and directionally moving the nano-particles is fulfilled. In the aspect of treatment, the effective concentration of the perfusion medicine is improved, deep penetration is carried out on the bladder tissue, a feasible scheme is provided for medicine delivery of deep tumor tissue, technical support and a new thought are provided for bladder perfusion treatment, and good application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedicine, and in particular relates to a nano drug hydrogel composite system capable of bladder instillation and application thereof. Background Art

[0002] As a urine storage device that connects the human body to the outside world, the bladder has its own special inspection and medication methods. As a way to treat bladder diseases, intravesical instillation allows drugs to act directly on the bladder mucosa, with little effect on other normal tissues. Intravesical instillation therapy is not only the most common auxiliary treatment for bladder cancer patients after surgery, but is also used to treat other common bladder diseases, such as interstitial cystitis, overactive bladder, urinary incontinence, chronic urinary tract infection, etc. However, studies in recent years have shown that intravesical instillation therapy cannot effectively reduce the postoperative recurrence rate of high-grade bladder tumors after transurethral bladder tumor resection, and the treatment effect on other common bladder diseases is also relatively limited.

[0003] The reasons that limit the efficacy of bladder instillation are the continuous dilution and flushing of the instilled drugs by urine, and the presence of multiple physiological barriers in the bladder cavity that affect the accumulation and absorption of drugs in the lesions. Among them, the mucus layer on the inner surface of the bladder cavity, as the first physiological barrier, can hinder the adhesion and penetration of drugs. In order to increase the residence time of drugs in the bladder, it is necessary to modify the drugs so that they can produce covalent (hydrogen bonds, electrostatic adsorption, disulfide bonds) or non-covalent interactions with the mucus layer, thereby improving the mucus adhesion of the drugs. However, paradoxically, the enhancement of the drug's adhesion to the mucus layer will reduce the drug's permeability to the mucus layer, so that it is trapped in the mucus layer and cannot penetrate into the urothelial tissue. Therefore, the drug needs to have both "mucus adhesion" and "mucus permeability" to overcome the barrier effect of the mucus layer.

[0004] The urothelial barrier is the second biological barrier. Usually, the mode of drug crossing the urothelial barrier is passive diffusion via the cell, but the transmembrane resistance of the urothelial barrier is much higher than other epithelial barriers. Therefore, drugs that rely on passive diffusion via the paracellular pathway cannot effectively cross the urothelial barrier to the deep bladder tissue. Certain physical methods (thermal penetration) and some chemical penetration enhancers can destroy the urothelial barrier, thereby improving the passive diffusion efficiency of drugs, but may cause cystitis. Drug delivery systems with active permeability can overcome the inefficiency limitations of passive diffusion and are the best choice for drugs to efficiently penetrate the urothelial barrier to deep tissues.

[0005] In bladder instillation therapy, a drug delivery system with active permeability can overcome the inefficiency limitations of passive diffusion and is the best choice for bladder instillation drugs to efficiently penetrate the urothelial barrier to deep into the tissue. In addition, bladder instillation drugs need to be able to remain in the bladder cavity for a long time to achieve long-term therapeutic effects.

[0006] Bladder instillation drug carriers need to have two key capabilities, one is the adhesion to bladder mucus, and the other is the ability to penetrate bladder tissue. In order to improve the adhesion of drug carriers to mucus, the carrier is generally modified, such as modifying the drug as a whole to be positively charged, and electrostatically adsorbing it with negatively charged mucus, thereby enhancing adhesion to mucus. However, the modified drug is easy to "retain" in the mucus layer and weaken the penetration into bladder tissue. The use of active penetration mechanism to promote the penetration of drugs into bladder tissue can effectively improve the penetration efficiency. The mechanism of active penetration includes three categories: transcytosis, direct contact transmission and self-driving. Among them, the self-driving delivery system (micro-nano motor) has become a hot spot in the study of hypertonic drug carriers in recent years because of its strong tissue permeability, high drug loading, and power not interfered by cell heterogeneity. In order to ensure that the micro-nano motor can achieve effective directional movement, the mainstream method often uses asymmetric modification of the power source on the surface of the micro-nano motor or constructs a micro-nano motor with asymmetric morphology. This type of micro-nano motor is called "Janus micro-nano motor". The construction methods of Janus micro-nano motors include layer-by-layer stacking, partial shielding, and exposure modification, etc. However, the preparation process of Janus micro-nano motors has high requirements, low yield, and many by-products, which is not conducive to clinical transformation, and has the following two major problems: 1) Complex modification methods: Existing Janus micro-nano motors use various methods to asymmetrically modify the power source on the surface. This modification method requires "shielding" half of the surface of the micro-nano motor to achieve the purpose of not modifying the power source in the "shielded" part. After the modification is completed, the "shielding" needs to be removed to make the micro-nano motor free. Since the modification requires many steps, the yield and by-products increase; 2) Uncontrollable movement of Janus micro-nano motors: Although the asymmetric modification of Janus micro-nano motors can make them produce effective movement, the direction of their movement is uncertain.

[0007] Therefore, there is an urgent need to find a bladder instillation drug carrier with simple preparation, high recovery rate, high adhesion, high permeability and guiding directional effect, so as to improve the accumulation and absorption of drugs in the lesion and improve the efficacy of bladder instillation. Summary of the invention

[0008] In order to solve the problems existing in the prior art, the present invention provides a nano drug hydrogel system that can be injected into the bladder and its application, optimizes the construction method of micro-nano motors, constructs a complex with high adhesion and permeability, makes the directional movement of nanoparticles controllable, and at the same time improves the accumulation and absorption of drugs in the lesions, thereby improving the efficacy of bladder instillation.

[0009] In order to achieve the above object, the present invention adopts the following scheme:

[0010] In one aspect, the present invention provides a complex comprising a hydrogel and urease-modified nanoparticles.

[0011] Furthermore, in the complex, the sol-gel state of the hydrogel can change with temperature. It is in a sol state at room temperature and changes into a gel state when the temperature rises to 35°C-37°C after injection into the bladder. It has phase transition properties and mucosal adhesion.

[0012] Furthermore, in the complex, drugs can be encapsulated in the nanoparticles, and the upper limit of the particle size is the pore size of the hydrogel, and there is no lower limit of the particle size.

[0013] In some embodiments, the hydrogels and nanoparticles that meet the above conditions can be used to construct the complex with high adhesion and permeability described in the present invention. While the preparation is simple, the practicability is strong, and the recovery rate is high, the nanoparticles can be guided to move in an orderly and directional manner, thereby increasing the effective concentration of the infused drug and deeply penetrating the bladder tissue.

[0014] Furthermore, the hydrogel includes any one or more of poloxamer 407, chitosan, hyaluronate, and alginate; the hydrogel also includes a disintegrant, and the disintegrant includes a salt that generates gas when exposed to acid; the salt that generates gas when exposed to acid includes any one or more of sodium bicarbonate, ammonium bicarbonate, calcium bicarbonate, or potassium bicarbonate.

[0015] In some embodiments, several hydrogels satisfying the above conditions are listed, but the invention is not limited to the listed types.

[0016] Preferably, the hydrogel comprises poloxamer 407, and the concentration of poloxamer 407 is 20%; the acid-generating salt comprises sodium bicarbonate.

[0017] In some embodiments, the concentration of poloxamer 407 is selected to be 20%, at which the sol-gel state transition with temperature change can be achieved.

[0018] In some embodiments, the disintegrants used in the hydrogel in the complex are screened, and it is found that when a salt that generates gas when exposed to acid (sodium bicarbonate) is selected as the disintegrant, the drug can be fully effective while the hydrogel decomposes at the fastest rate, reducing the obstruction of the normal lumen of the urinary tract.

[0019] Furthermore, a symmetrical modification method is used to uniformly modify the urease on the surface of the nanoparticles; the modification method is to couple the urease to the nanoparticles via a linker.

[0020] In some embodiments, the inventors conducted characterization studies on urease modification of the nanoparticles, and the results showed that there was no statistically significant difference in the urease activity of the modified nanoparticles compared with the free urease activity.

[0021] Furthermore, the nanoparticles include any one or more of membrane nanoparticles, hollow silica nanoparticles, and exosome nanoparticles; the linkers include any one or more of biotin-chain and avidin-biotin, NHS-PEG2-Maleimide, and N-(p-Maleimidophenyl)isocyanate.

[0022] Preferably, the nanoparticles comprise membrane nanoparticles; and the linkers comprise biotin-streptavidin-biotin.

[0023] In some embodiments, several nanoparticles and linkers that meet the above conditions are listed, but are not limited to the listed types, and the linkers vary with the properties of the nanoparticles.

[0024] On the other hand, the present invention provides a use of the complex as described in any one of the above technical solutions for preparing a preparation of a directional carrier for bladder instillation of drugs, and the use is achieved in the following manner: using the hydrogel as a drug loading platform, forming a concentration gradient through the penetration of urea, so that the nanoparticles modified with a power source in the hydrogel produce directional movement due to the difference in the magnitude of the driving force on both sides, so that the disorderly moving nanoparticles are restricted by external conditions to achieve the purpose of orderly and directional movement.

[0025] In some embodiments, the permeability of the complex constructed by the present invention to the bladder physiological barrier and the urothelial barrier was tested respectively, and the results showed that the mucus penetration efficiency of the complex constructed by the present invention was high, and within a certain range, as the urea concentration increased, the permeability of the complex to bladder mucus became stronger, further demonstrating the feasibility of the complex of the present invention in bladder perfusion.

[0026] In another aspect, the present invention provides a use of a hydrogel for preparing a preparation of a directional carrier for bladder instillation of drugs, wherein the hydrogel encapsulates urease-modified nanoparticles, and the nanoparticles can encapsulate drugs, and the upper limit of the particle size is the pore size of the hydrogel, and there is no lower limit of the particle size.

[0027] In another aspect, the present invention provides a use of nanoparticles for preparing a preparation of a directional carrier for bladder instillation of drugs, wherein the nanoparticles can encapsulate drugs, and the upper limit of the particle size is the pore size of the hydrogel, and there is no lower limit of the particle size.

[0028] The beneficial effects of the present invention are:

[0029] 1. The inventors have constructed a complex of urease-symmetrically modified nanoparticles encapsulated in a hydrogel, which has high adhesion to bladder mucus and strong permeability, reduces the impact of dilution and flushing, and improves the accumulation and absorption of drugs at the lesion site;

[0030] 2. Compared with asymmetrically modified micro-nanomotors, the complex of the present invention has the characteristics of simple preparation, strong practicality, few by-products, high yield and high recovery rate, while retaining the directional movement ability of asymmetrically modified nanoparticles, providing the possibility for clinical transformation;

[0031] 3. At the same time, the complex of the present invention adds hydrogel, which plays a guiding role in directional movement, allowing the nanoparticles to move fixedly from the bladder cavity to the bladder wall.

[0032] 4. Urea forms a concentration gradient decreasing from the bladder cavity to the bladder wall in the complex through passive diffusion, forming an asymmetric concentration distribution at both ends of the nanoparticles. After the urease on the surface of the nanoparticles decomposes the urea, the driving force strength at both ends is different, which causes the nanoparticles to move directionally along the urea concentration gradient in the hydrogel.

[0033] 5. The present invention provides a new concept for bladder instillation drugs, that is, using hydrogel as a drug-carrying platform and combining it with urease-modified nanoparticles to form a complex with high adhesion and permeability, so that the nanoparticles move in an orderly and directional manner, thereby increasing the effective concentration of the instilled drug and deeply penetrating the bladder tissue, providing a feasible solution for drug delivery to deep tumor tissues, and also providing technical support and new ideas for bladder instillation treatment, which has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The figure is a flow chart of the construction and injection of the complex of the present invention.

[0035] Figure 2 a is the viscosity of the self-degradable hydrogel observed by naked eyes.

[0036] Figure 2 b shows the disintegration of the hydrogel solution in artificial urine.

[0037] Figure 2 c is the pore distribution of hydrogel under transmission electron microscopy.

[0038] Figure 3 a: The modification of nanoparticles with fluorescently labeled urease.

[0039] Figure 3 b is the detection of urease activity after modification.

[0040] Figure 3 c is the Zeta potential detection of the synthetic product.

[0041] Figure 4 a is the model of Transwell chamber for detecting the penetration efficiency of nanomotors.

[0042] Figure 4b is the permeation efficiency of the complex (P@UMN) with different solutes in the upper chamber.

[0043] Figure 4 c is the mucus penetration efficiency of the complex (P@UMN) at a concentration gradient of urea.

[0044] Figure 4 d is the mucus penetration efficiency of the complex (P@UMN) with different urea addition methods.

[0045] Figure 5 a is the penetration depth in each layer from the middle layer to the bottom surface of the 3D cell spheroid.

[0046] Figure 5 b: Cross-sectional fluorescence quantification of the middle layer of the 3D cell spheroid.

[0047] Figure 5 c: Total fluorescence quantification of the middle layer of 3D cell spheroids. DETAILED DESCRIPTION

[0048] The present invention is further described in detail below in conjunction with the examples. It should be pointed out that the examples described below and the materials used therein are intended to facilitate the understanding of the present invention and do not have any limiting effect thereon.

[0049] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0050] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0051] Example 1 Construction of hydrogel and urease-modified nanoparticle complex (H@UN)

[0052] Bladder instillation drug carriers need to have two key capabilities, one is the adhesion to bladder mucus, and the other is the ability to penetrate bladder tissue. In order to improve the adhesion of drug carriers to mucus, the carrier is generally modified, such as modifying the drug as a whole to be positively charged, and electrostatically adsorbing it with negatively charged mucus, thereby enhancing adhesion to mucus. However, the modified drug is easy to be "retained" in the mucus layer and weakens the penetration into bladder tissue. The asymmetric modification of the power source on the surface of the micro-nanomotor can achieve effective movement and improve the penetration efficiency into the tissue, but on the one hand, the construction method is complex, the preparation process requirements are high, the yield is low, and there are many by-products, which is not conducive to clinical transformation; on the other hand, although it can produce movement, the direction of its movement is uncertain, and it can move in any direction around in the bladder cavity.

[0053] Therefore, the inventors constructed a complex of urease-modified nanoparticles encapsulated in a hydrogel, in which urease was symmetrically modified on the surface of the nanoparticles. On the one hand, the complex has high adhesion to bladder mucus and strong permeability. On the other hand, while having the characteristics of simple preparation, strong practicability, few by-products, high yield and high recovery rate, it retains the mobility of asymmetrically modified nanoparticles, providing the possibility for clinical transformation. On the other hand, it has a guiding directional movement ability, which enables the nanoparticles to move fixedly from the bladder cavity to the bladder wall.

[0054] The screening and construction method of the complex of hydrogel and urease-modified nanoparticles is as follows. Figure 1 As shown (the experimental process takes poloxamer 407 and membrane nanoparticles as an example, but the hydrogel and nanoparticles of the present invention are not limited to this):

[0055] 1. Screening of hydrogels:

[0056] 1) The sol-gel state of the hydrogel of the present invention can change with temperature. It is in a sol state at room temperature and changes into a gel state when the temperature rises to 35°C-37°C after injection into the bladder. It has phase transition properties and mucosal adhesion: In this embodiment, the concentration of poloxamer 407 is controlled to be 20%. When injected into the bladder with a syringe, its state is sol-like and has a certain fluidity. After being injected into the bladder, due to the increase in temperature, its sol is converted into a gel state and adheres to the mucus surface of the bladder, providing time for the directional movement of the urease-modified nanoparticles (UN).

[0057] like Figure 2 As shown in a, Figure 2 a is the adhesion of the hydrogel in urine observed with the naked eye.

[0058] 2) Having water solubility and suitable decomposition rate: In this embodiment, under the premise that the hydrogel has a certain water solubility, in order to further adjust the decomposition rate of the hydrogel, under the premise of ensuring that the drug is fully effective, disintegrants (sodium bicarbonate, a granular salt that generates gas when exposed to acid) are added exogenously. The disintegrants react with hydrogen ions in urine to disintegrate the structure of the hydrogel, promote its disintegration, and thus reduce the obstruction effect on the normal cavity of the urinary tract.

[0059] like Figure 2 As shown in b, Figure 2 b is the disintegration of the hydrogel solution in artificial urine. Figure 2 As can be seen in b, the disintegration rate of the hydrogel is controllable, and after 4 hours, the hydrogel has basically disintegrated.

[0060] In this example, it was found that poloxamer 407, chitosan, hyaluronate and alginate can all be used as hydrogels to construct the complex of the present invention, and in comparison, the selection of poloxamer 407 enables the complex to have a better decomposition rate and directional movement ability.

[0061] 2. Screening of drug-loaded nanoparticles:

[0062] 1) Drugs can be encapsulated in nanoparticles, and the particle size and hardness must be moderate, with the upper limit not exceeding the size of the hydrogel cavity itself, and no lower limit on the particle size. Taking poloxamer 407 as an example, its pore size is 4 μm, and the particle size of nanoparticles is generally between 200 and 1000 nm;

[0063] 2) Nanoparticles must also have a certain degree of deformation ability in order to move smoothly in the complex hydrogel cavity.

[0064] like Figure 2 As shown in c, Figure 2 c is the pore distribution of the hydrogel under transmission electron microscopy (Scale bar: 4 μm). The particle size of the nanoparticles should be smaller than the pore size of the hydrogel.

[0065] In this example, it was found that membrane nanoparticles, hollow silica nanoparticles, exosome nanoparticles, etc. can all be used as nanoparticles to construct the complex of the present invention, and in comparison, the selection of membrane nanoparticles enables the complex to have better directional movement ability.

[0066] 3. Modification of urease:

[0067] The nanoparticles are co-incubated with urease, and the two are coupled through a linker so that the urease is symmetrically and evenly modified on the surface of the nanoparticles. The linker varies with the properties of the nanoparticles, including biotin-streptavidin-biotin, NHS-PEG2-Maleimide, and N-(p-Maleimidophenyl)isocyanate.

[0068] like Figure 3 a. Figure 3 As shown in c, Figure 3 a and Figure 3 c is the successful modification of urease to membrane nanoparticles by UV-spectrophotometer detection and determination of the Zeta potential of each modification product; Figure 3 In a, MN is membrane nanoparticles, Urease is urease, and UMN is urease-modified membrane nanoparticles; Figure 3 In c, MN (Membrane nanoparticle) is a membrane nanoparticle, MN@bio is a membrane nanoparticle linked to biotin, MN@bio@stre is a membrane nanoparticle linked to biotin-streptavidin, and UMN is a urease-modified nanoparticle. After successful modification, the urease activity of the membrane nanoparticles was measured, and the results showed that there was no statistically significant difference between the urease activity and the free urease activity. Figure 3As shown in b, Free urease is free urease, Immobilized urease is successfully modified urease, and the vertical axis is biological activity.

[0069] In this embodiment, according to the properties of membrane nanoparticles, biotin-streptavidin-biotin is preferably used as a linker.

[0070] The urease-modified nanoparticles as described above are encapsulated in the hydrogel to obtain the complex of the present invention. The hydrogels that meet the above conditions include poloxamer 407, chitosan, hyaluronate, and alginate; and the nanoparticles that meet the above conditions, including membrane nanoparticles, hollow silica nanoparticles, and exosome nanoparticles, can all be used to construct the complex of the present invention. The hydrogel is used as a drug-carrying platform to allow the nanoparticles loaded with drugs to move in an orderly and guided manner from the bladder cavity to a certain part of the bladder wall, thereby increasing the effective concentration of the infused drug and deeply penetrating the bladder tissue, providing a feasible solution for drug delivery to deep tumor tissues.

[0071] Example 2 Testing of the permeability of the complex to the bladder physiological barrier

[0072] In order to verify that the complex constructed in Example 1 has good permeability to the bladder physiological barrier (the experimental process takes poloxamer 407 and membrane nanoparticles as an example, but the hydrogel and nanoparticles of the present invention are not limited to this), in this example, pig bladder mucus is scraped and placed in the upper chamber of the Transwell chamber. After standing for 5 minutes, the complex (P@UMN) is added. After it solidifies, urea solution is added to the surface, such as Figure 4 As shown in a, Urea is urea solution, Compositehydrogel is a complex, Porcine bladder mucosa is porcine bladder mucosa, and Permeable Drug is a permeable drug. Figure 4 As can be seen in a, after the addition of urea solution, the complex passed through the pig bladder mucus and entered the lower chamber. Figure 4 b and Figure 4 d: The urea solution was placed on the surface of the complex to generate a concentration gradient, and urea and the complex were premixed as a control to explore the penetration efficiency of urease-modified nanoparticles (UMN) into bladder mucus.

[0073] Figure 4 In b, PBS and Urine are different upper chamber solutes, MN is nanoparticles, UMN is urease-modified nanoparticles, P@MN is a complex of hydrogel and nanoparticles, and P@UMN is a complex of hydrogel and urease-modified nanoparticles. The ordinate is the penetration efficiency. Figure 4As can be seen from b, 1) when the solute in the upper chamber is urine, the penetration efficiency of the urease-modified nanoparticles is significantly improved; 2) at the same time, after the addition of hydrogel, the penetration efficiency of the complex (P@UMN) is significantly improved again compared with the urease-modified nanoparticles, reaching 55% (** indicates P < 0.01, **** indicates P < 0.0001).

[0074] Figure 4 In d, Premixed is the premixed group, Add later is the group with urea solution added later, and the ordinate is the fluorescence intensity (equivalent to the permeation efficiency, the membrane nanoparticles are fluorescently labeled and the permeation efficiency is calculated). Figure 4 As shown in d, there is a significant difference between the group with concentration gradient produced by adding urea solution later and the premixed group, P<0.01, indicating that the penetration efficiency of the group with concentration gradient produced is significantly improved.

[0075] Figure 4 c is the variation of the permeation efficiency of the complex with the urea concentration. Figure 4 As can be seen in c, as the surface urea concentration increases within a certain range, the penetration of the complex (P@UMN) into bladder mucus becomes stronger.

[0076] It can be seen that the complex of hydrogel and urease-modified nanoparticles constructed in Example 1 has 1) a very significant improvement in penetration efficiency when a concentration gradient is generated in the bladder cavity; 2) a significant improvement in penetration efficiency compared to urease-modified nanoparticles without the addition of hydrogel; 3) within a certain range, the penetration efficiency of the complex (P@UMN) increases with increasing urea concentration.

[0077] Example 3 Testing of the permeability of the complex to the urothelial barrier

[0078] In order to further explore the permeability of the complex constructed in Example 1 to the urothelial barrier, a 3D cell spheroid model was established in the present invention, and the membrane nanoparticles were fluorescently labeled (the experimental process took poloxamer 407 and membrane nanoparticles as an example, but the hydrogel and nanoparticles of the present invention are not limited to this):

[0079] Figure 5 a is the penetration depth in each layer from the middle layer to the bottom layer of the 3D cell spheroid (Scale bar: 100 μm). Figure 5 As shown in a, the penetration amount and range of the complex (P@UMN) group on the 3D cell sphere were significantly higher than those of other groups; Figure 5 b is the cross-sectional fluorescence quantification of the middle layer of the 3D cell spheroid; Figure 5 As can be seen in b, the cross-sectional fluorescence intensity of the middle layer of the 3D cell sphere in the complex (P@UMN) group was significantly higher than that in other groups; Figure 5c is the total fluorescence quantification of the middle layer of the 3D cell spheroid. Figure 5 As can be seen from c, the penetration depth of the complex (P@UMN) group into the 3D cell sphere was significantly higher than that of other groups.

[0080] It can be seen that the complex of hydrogel and urease-modified nanoparticles constructed in Example 1 has significantly improved penetration amount and penetration depth of 3D cell spheres compared with the other groups, further demonstrating the feasibility of the complex in bladder perfusion.

[0081] Example 4 Comparative test with addition of disintegrant

[0082] In order to construct the complex of the hydrogel and urease-modified nanoparticles in Example 1, on the basis of the good water solubility of the hydrogel, in order to further adjust the decomposition rate of the hydrogel so that the drug can fully take effect while the hydrogel will disintegrate to reduce the obstruction of the normal urinary tract, a comparative test of exogenous addition of disintegrants was carried out in this example, and there are several ways (the experimental process takes poloxamer 407 and membrane nanoparticles as an example, but the hydrogel and nanoparticles of the present invention are not limited to this; it is known that the drug is fully effective within 4 hours):

[0083] 1. Add acid-generating salt (sodium bicarbonate) as a disintegrant;

[0084] 2. No disintegrant is added.

[0085] The results are shown in Table 1:

[0086] Table 1 Effect of disintegrant on the decomposition rate of the complex

[0087]

[0088]

[0089] As can be seen from Table 1, when no disintegrant is added, the complex of the present invention completely disintegrates in about 12 hours; when a salt (sodium bicarbonate) that generates gas when exposed to acid is added as a disintegrant, the complex of the present invention completely disintegrates in about 5 hours. At the same time, it is known that the drug has fully taken effect in about 4 hours. Therefore, under the premise of ensuring that the drug fully takes effect, the complex with the addition of a disintegrant can completely disintegrate in a shorter time, reducing the obstruction effect on the normal cavity of the urinary tract.

[0090] Therefore, the present invention selects to add exogenous disintegrants (salts that generate gas when exposed to acid) to ensure that the drug is fully effective. The disintegrant reacts with hydrogen ions in urine to disintegrate the structure of the hydrogel and promote its disintegration, thereby reducing the obstruction effect on the normal cavity of the urinary tract.

[0091] Example 5 Screening of disintegrants

[0092] In order to construct the complex of the hydrogel and urease-modified nanoparticles in Example 1, on the basis of the good water solubility of the hydrogel, in order to further adjust the decomposition rate of the hydrogel so that the drug takes effect for a long time and the hydrogel will disintegrate to reduce the obstruction of the normal urinary tract, the exogenously added disintegrant was screened in this example, and there are several ways (the experimental process takes poloxamer 407 and membrane nanoparticles as examples, but the hydrogel and nanoparticles of the present invention are not limited to this; in this example, sodium bicarbonate, ammonium bicarbonate, calcium bicarbonate, potassium bicarbonate, four acid-generating salts are used as disintegrants for testing, but the disintegrants that can be selected in the present invention are not limited to this) (it is known that the drug has completely taken effect within 4 hours):

[0093] 1. Sodium bicarbonate;

[0094] 2. Ammonium bicarbonate;

[0095] 3. Calcium bicarbonate;

[0096] 4. Potassium bicarbonate.

[0097] The results are shown in Table 2:

[0098] Table 2 Decomposition rate of the complex by different disintegrants

[0099]

[0100] As can be seen from Table 2, the compound with potassium bicarbonate added has the fastest decomposition rate, while the compound with calcium bicarbonate added has the slowest decomposition rate. It is known that the drug has fully taken effect within 4 hours, so if the fastest decomposition rate is selected as the disintegrant, the drug cannot fully take effect; if the slowest decomposition rate is selected as the disintegrant, it is more likely to cause blockage of the normal urinary tract.

[0101] It can be seen that the above acid-generating salts can all be used as disintegrants in the present invention. However, in comparison, sodium bicarbonate is selected as a disintegrant, which allows the drug to fully take effect while making the hydrogel decompose at the fastest rate, thereby reducing the obstruction effect on the normal lumen of the urinary tract.

[0102] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A complex, It is characterized in that Comprising hydrogel and urease-modified nanoparticles.

2. The composite according to claim 1, It is characterized in that The sol-gel state of the hydrogel can change with temperature. It is in a sol state at room temperature, and changes into a gel state when the temperature rises to 35° C.-37° C. after being injected into the bladder. It has phase transition properties and mucosal adhesion.

3. The composite according to claim 2, It is characterized in that The nanoparticles can contain drugs, and the upper limit of the particle size is the pore size of the hydrogel, and there is no lower limit of the particle size.

4. The composite according to claim 3, It is characterized in that The hydrogel includes any one or more of poloxamer 407, chitosan, hyaluronate, and alginate; the hydrogel also includes a disintegrant, and the disintegrant includes a salt that generates gas when exposed to acid; the salt that generates gas when exposed to acid includes any one or more of sodium bicarbonate, ammonium bicarbonate, calcium bicarbonate, or potassium bicarbonate.

5. The complex according to claim 4, It is characterized in that The hydrogel includes poloxamer 407, and the concentration of poloxamer 407 is 20%; the acid-generating salt includes sodium bicarbonate.

6. The composite according to claim 5, It is characterized in that The urease is uniformly modified on the surface of the nanoparticles by using a symmetrical modification method; the modification method is to couple the urease with the nanoparticles through a linker.

7. The complex according to claim 6, It is characterized in that The nanoparticles include any one or more of membrane nanoparticles, hollow silica nanoparticles, and exosome nanoparticles; the linkers include biotin-streptavidin-biotin, NHS-PEG 2 -Maleimide, N-(p-Maleimidophenyl)isocyanate, or any one or more thereof.

8. The complex according to claim 7, It is characterized in that The nanoparticles include membrane nanoparticles; the linkers include biotin-streptavidin-biotin.

9. Use of the complex according to any one of claims 1 to 8 for preparing a preparation of a drug carrier for bladder instillation, It is characterized in that The use is achieved in the following manner: the hydrogel is used as a drug-carrying platform, and a concentration gradient is formed through the penetration of urea, so that the nanoparticles modified with a power source in the hydrogel produce directional movement due to the difference in the magnitude of the driving force on both sides, and the disorderly moving nanoparticles are restricted by external conditions to achieve the purpose of orderly and directional movement.

10. Use of a hydrogel for preparing a directional carrier preparation for bladder instillation of drugs, It is characterized in that The hydrogel contains urease-modified nanoparticles, and drugs can be contained in the nanoparticles. The upper limit of the particle size is the pore size of the hydrogel, and there is no lower limit of the particle size.

Citation Information

Cited By

  • Hydrogel serving as drug carrier during bladder drug perfusion as well as preparation method and application of hydrogel

    CN121622557A

  • Self-driven bacillus calmette-guerin vaccine-nano enzyme compound and preparation method thereof

    CN121926966A